Experimental results of 144-element dual-polarized endfire tapered-slot phased arrays. - Holter, H. (IEEE Transactions on antennas and propagation)
Two 9×8×2 (144 element) dual-polarized endfire tapered-slot phased arrays have been built. Measured data for mutual coupling coefficients and scan-element patterns are presented. Also, element resonances, predicted by numerical infinite-array analysis are examined. The dimensions of the two arrays are identical. They differ in that plated-through vias have been repositioned to eliminate element resonances. One array was expected to operate from 1.0 to 4.6 GHz and the other from 1.0 to 5.9 GHz. It was found that, at low frequencies, the central elements are heavily affected by the finiteness of the arrays due to strong mutual coupling between array elements. Extrapolation of the observations indicates that a tapered-slot phased array, designed for wide-angle scanning, should be comprised of at least 30-40 rows and columns of elements to obtain low-frequency performance that is comparable to infinite-array predictions. In spite of the smallness of the array, predicted-element resonances could be identified by examination of the phase of the mutual coupling coefficients. Based on these observations, the plated-through vias are adequate to remove element resonances